Smart Healthcare Wearable Device for Early Disease Detection Using Machine Learning - Damre, Suraj S.; Shendkar, Bhagyashree D.; Kulkarni, Nikita; Chandre, Pankaj R.; Deshmukh, Sayalee (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The present invention introduces a breakthrough in healthcare technology by unveiling a novel Smart Healthcare Wearable Device for Early Disease Detection using advanced Machine Learning algorithms. This wearable device seamlessly integrates cutting-edge sensor technology, real-time data analytics, and intelligent machine learning models to empower individuals with early detection capabilities for potential health issues. The Smart Healthcare Wearable Device is equipped with a diverse array of sensors, collecting an array of vital health metrics such as heart rate, blood pressure, oxygen saturation, and body temperature. These sensors continuously monitor the wearer’s physiological parameters, enabling real-time data acquisition for comprehensive health insights. The innovation lies in the implementation of machine learning algorithms that harness the collected data to recognize subtle deviations from baseline health patterns. These algorithms, trained on vast datasets, exhibit the capacity to identify early indicators of diseases and health anomalies, even before overt symptoms manifest. The machine learning models continuously evolve through an adaptive learning process, enabling the device to tailor its detection capabilities to each individual user. Upon detecting potential health concerns, the Smart Healthcare Wearable Device employs an alert mechanism, immediately notifying the wearer and authorized healthcare providers. This swift alert system enables timely medical intervention, potentially circumventing disease progression and improving treatment outcomes. Furthermore, the device enriches user experience through personalized health recommendations. Leveraging the data-driven insights provided by the machine learning models, the wearable offers activity suggestions, sleep optimization strategies, and dietary advice, promoting proactive wellness management. The Smart Healthcare Wearable Device for Early Disease Detection addresses a critical need for preventive healthcare solutions in an era where early intervention is pivotal. By merging sensor technology and machine learning prowess, this invention introduces a transformative paradigm in healthcare, ultimately enhancing users’ quality of life and well-being.